(untitled) (Eurasian Journal of Philology Science and Education, 2021)
Language policy is understood as ensuring national unity, economic conditions and political reasons for interfering with the forms and functions of language within the framework of political powers. We can also express the status, languages, and regions of the languages spoken in a society as a set of ideas, laws, and decisions about the rights of individuals who speak them. Although the concepts of «language policy» and «language planning» are accepted as a new concept in sociolinguistics, they are rooted in the past. It should be noted that there is no single term that can express this concept among researchers conducting research in this field related to language policy and language planning. «Language policy, language planning» is often used as a different, sometimes the same concept. Language regulation is a concept that encompasses the whole of conscious activities related to the structure, position, use, and function of languages. However, it is a multifaceted chain of activities involving different processes, expressed in different terms, such as language regulation, language policy, language planning. These vary depending on whether the intervention consists of specific ideas or an abstract action plan, whether the activities are aimed at language norms or the status of the language. The first stage of language regulation is the assessment process aimed at identifying language, languagesociety problems. The problems that arise are considered. The next stage, language policy, is the most concrete stage of a regulatory activity, consisting of goal setting. Language planning is the activity of concretely implementing language policy. Language policy is a set of decisions and applications aimed at the languages spoken in a political unit, their areas, development and use. The main feature of language policy is the presence of conscious interference from outside. These external interferences focus on the internal structure of a language.